STRUCTURE AND EVOLUTION OF THE PROTOTYPE MAGNETIC CATACLYSMIC VARIABLE AM HER: CLUES FROM X-RAY (CHANDRA) AND OPTICAL POLARIMETRY AND PHOTOMETRY. FOUR-COMPONENT MODEL OF THE AUTO-CORRELATION FUNCTION - Andronov, I. L; Burwitz, V.; Reinsch, K.; Barwig, H.; Chinarova, L. L.; Kolesnikov, S. V.; Shakhovskoy, N. M.; Hambaryan, V.; Beuermann, K.; Yuhanov, D. A. (Одеські астрономічні публікації, 2017)
In this paper, we present the results of a study of the variability of the prototype polar AM Her using one of the complementary mathematical methods. Results of modeling of the auto-correlation analysis of a 24117 second long Chandra observation are discussed. The data have been binned to 1-second intervals. The corresponding auto-correlation func- tion has been modeled to take into account the nonsinusoidal orbital variability of the object, onto which a strong flickering is added. The model of a second order trigonometric polynomial (orbital) + a first-order Auto-Regressive process (”shot-noise” flickering) does not seem to be not sufficient. A much better approximation can be achieved With a a four-parameter fit With exponential decay times t1 : 174s and t-2 : 9.8s. A possible physical mechanism may be attributed to the longer time of the flare of the plasma blob (” spaghetti”) falling onto the White dwarf as compared to flares corresponding to smaller blobs resulting from magneto- hydrodynamical instabilities. The results are compared vvith numerical models. .